The effect of environmental pH change on bovine articular cartilage metabolism: implications for the use of buffered solution during arthroscopy? - (:unkn) unknown (SPRINGER, 2014)
The purpose of this study is to determine the immediate effects of pH change on the metabolism of bovine chondrocytes. Bovine osteochondral explants were pre-cultured and placed in Ringer's lactate solution. Thirty explants were randomly divided into 3 groups. Buffered Ringer's lactate, pH 7.2, was used in Group I; buffered Ringer's lactate, pH 7.4 (normal bovine knee joint pH), was used in Group II; and this group was also set as the control group. Buffered Ringer's lactate, pH 7.6, was used in Group III. All specimens were soaked for 2 h. RNA yield analyses were performed to evaluate the changes in cartilage metabolism at different pH levels. Mean RNA yields of (hypoxia-induced factor) 1 alpha that were immersed at pH 7.2 and 7.6 were 10.5- and 9.9-fold from base, respectively, which were lower compared to explants at pH 7.4 which was found as 15.2-fold. Mean RNA yields of aggrecan that were immersed at pH 7.2 and 7.6 were 12.2- and 13.6-fold from base, respectively, which were lower compared to explants at pH 7.4 which was found as 20-fold. RNA yields of collagen type II at pH 7.2 and 7.6 were 16.1- and 16.6-fold from base, respectively, which were lower compared to explants immersed at pH 7.4 which was found as 22.1-fold. The findings of the presented study suggest that short-term exposures to both acidic and basic pH may have effects on chondrocyte function. Our findings also indicate that exposures to solutions with a pH different from normal by only 0.2 unit could suppress chondrocyte metabolism and RNA synthesis. Using buffered irrigation solutions with a pH closer to the normal joint pH could be more physiologic and causes less ultra-structural damage than regular irrigation solutions. II.
Keywords: Cartilage; pH; Metabolism; Irrigation; Buffer; Solution; DIFFERENT TEMPERATURES; IRRIGATION FLUIDS; CHONDROCYTE